Political Participation : Empowering Women in Malaysia (1980-2013) = (Political Participation: Empowering Women in Malaysia (1980-2013) - Nor Rafidah, Saidon; Sity, Daud; Mohd, Samsudin (Universiti Kebangsaan Malaysia, 2017)
This study discusses the empowerment of women in the leadership of political involvement in Malaysia for the period between 1980 to 2013. The purpose of this study was to explain the awareness of women on the importance of empowerment of women in the leadership of political involvement in Malaysia. The research method used was qualitative methods through observations and interviews with some respondents selected apart from secondary data related to this study. Data from reliable sources are analyzed qualitatively. Based on the concept of leadership theories and gender, the study found that the empowerment of women in the leadership of political involvement can provide awareness of the importance of women as a gender balance in decision-making an administration. Indirectly gender gap can be reduced and eliminated.